Comparative Analysis of India, China, the United States, and the United Kingdom : Rising Leadership of India in Climate Change (1750 – 2020) - Sinha, Manoj; Sangwan, Tripti (Prabandhan: Indian Journal of Management, 2022)
This paper is a comparative study of 270 years (1750 – 2020) highlighting the impact of India, China, the United States, and the United Kingdom on the environment by assessing these countries on six parameters of cumulative CO2 emissions, production and consumption of CO2 emissions, CO2 emissions per unit, annual CO2 emissions, energy intensity, and share of these countries in global CO2 emissions. Further, the study showed, via empirical estimation of time series data by forming a linear regression model and using advanced statistical software, that even though India is developing at a fast pace, its income (GDP) elasticity of CO2 emissions is significantly low compared to other developing Asian countries (China) and developed economies (the United States and the United Kingdom), which grew at the cost of the environment. Henceforth, this paper provided an in-depth analysis of the sustainable ancient practices followed in India and discussed modern India’s pioneering policies, programs, and its transition from a linear to a circular economy to promote green economic growth and development, hence showing a path to the world to promote GDP without adverse impact on the climate and peaceful co-existence of humans and all other species on the planet.